1976
DOI: 10.1104/pp.57.1.15
|View full text |Cite
|
Sign up to set email alerts
|

Incorporation of Cytokinin N6-Benzyladenine into Tobacco Callus Transfer Ribonucleic Acid and Ribosomal Ribonucleic Acid Preparations

Abstract: The incorporation of the cytokinin N6-benzyladenine into tobacco (Nicotiana tabacum) callus tRNA and rRNA preparations isolated from tissue grown on medium containing either N6-benzyladenine-8_-4C or N6 -benzyladenine -8 14C: benzene-3H(G) has been examined. N6-benzyladenine was incorporated into both the tRNA and rRNA preparations as the intact base. Over 90% of the radioactive N6 -benzyladenosine recovered from the RNA preparations was associated with the rRNA. Purification of the crude rRNA by either MAK ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

1977
1977
1989
1989

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…While tRNA has been the prime candidate for cytokinin generation by polynucleotide turnover, N6-modified adenosines have been found as rare components of some ribosomal RNAs (42)(43)(44)(45)(46)(47), and the direct incorporation of exogenous cytokinins into tRNA, rRNA, and polyadenylylated mRNA has been reported in tobacco cells (33,(42)(43)(44)(45)(47)(48)(49). This incorporation is relatively low and may result from transcriptional errors in the presence of high levels of the adenosine derivatives (43).…”
Section: Resultsmentioning
confidence: 99%
“…While tRNA has been the prime candidate for cytokinin generation by polynucleotide turnover, N6-modified adenosines have been found as rare components of some ribosomal RNAs (42)(43)(44)(45)(46)(47), and the direct incorporation of exogenous cytokinins into tRNA, rRNA, and polyadenylylated mRNA has been reported in tobacco cells (33,(42)(43)(44)(45)(47)(48)(49). This incorporation is relatively low and may result from transcriptional errors in the presence of high levels of the adenosine derivatives (43).…”
Section: Resultsmentioning
confidence: 99%
“…This aspect was not investigated in this study. Small quantities of BA have, however, been shown to be incorporated into poiynucleotidies in other systems (Walker et al 1974, Armstrong et al 1976. The fact that the major metabolite, which persisted in Picea embryos, gave chromatographic evidence indicating that it was BA-nucleotide, clearly indicates that more attention must be given to this aspect or at least to the fact that BA action may be mediated via its nucleotide.…”
Section: Discussionmentioning
confidence: 99%
“…A long standing controversy concerns the functional involvement of cytokinins in RNA (Kende and Tavares 1968, Key 1969, Burrows 1975). Recent studies of cytokinin metabolism using tissue culture have demonstrated incorporation of intact cytokinins into RNA (Fox and Chen 1967, Walker et al 1974, Armstrong et al 1976). This incorporation followed long periods of incubation.…”
Section: Discussionmentioning
confidence: 99%